Performance of Lac Insect Kerria lacca Kerr on Bushy Host Flemingia semialata (Roxb.) - Bhagyapriya, P.; Rao, S. R. Koteswara; Sanyasidhurua; Ramesh, D. (International Journal of Economic Plants, 2025)
The study was carried out to assess the potential of Flemingia semialata as host of lac insect at Agriculture College, Bapatla, Andhra Pradesh (522101) India during January to June, 2023 to investigate the potential of F. semialata under coastal conditions of Andhra Pradesh. Among different productivity parameters, initial density of settlement (Number per square cm), final density of settlement (Number per square cm)., sex ratio (% of male insects), density at crop maturity (Number per square cm) were recorded high at lower stem portion of the host plant F. semialata compared to upper and middle stem portions. Initial mortality (%) was recorded high at upper portion of host plant compared to middle and lower portions. Mean fecundity (Number of young ones produced by the female insect) recorded was 389.60. Mean yield (kg) of brood lac obtained was 0.76 kg and mean yield (kg) of scrapped lac obtained was 0.35 kg. Mean female size was recorded as 1.85mm. Mean broodlac-scraped lac ratio recorded was 2.17. Among the life cycle parameters of Lac insect mean sex ratio varied from 22.66 to 25.29. The life period of female was recorded as 156 days. The mean fecundity of female was 380.96 crawlers. There was a positive non-significant correlation recorded between female lac cell size and fecundity and also between female lac cell size and female cell weightand concluded that F. semialata can be used as a potential host for lac cultivation in the state of Andhra Pradesh